Assessment of cerebral autoregulation using continuous-wave near-infrared spectroscopy during squat-stand maneuvers in subjects with symptoms of orthostatic intolerance - Kim, Jae-Myoung; Choi, Jong-Kwan; Choi, Mingyu; Ji, Minsu; Hwang, Gunpil; Ko, Sang-Bae; Bae, Hyeon-Min (Scientific reports, 2018)
Orthostatic lightheadedness in healthy young adults often leads to syncope in severe cases. One suggested underlying mechanism of orthostatic lightheadedness is a drop in transient blood pressure (BP); however, a decrease in BP does not always lead to a drop in cerebral blood flow (CBF) due to cerebral autoregulation (CA). We present a direct assessment method of CA using a multichannel continuous-wave near-infrared spectroscopy (CW-NIRS) device that measures the temporal changes in oxy- and deoxy-hemoglobin concentrations in the prefrontal cortex. Twenty healthy young adults were recruited. During the experiment, continuous beat-to-beat BP and heart rate were simultaneously measured during repetitive squat-stand maneuvers. We introduce a new metric termed ‘time-derivative hemodynamic model (DHbT)’, which is the time-derivative of total-hemoglobin concentration change that reflects the changes of cerebral blood volume and CBF. Although the absolute levels and the variations of systolic and diastolic BPs and mean arterial pressure showed no significant difference between the two groups, the proposed model showed a distinct difference in slope variation and response time of DHbT between the subjects with frequent symptom of orthostatic intolerance and the healthy control subjects. Thus, these results clearly demonstrate the feasibility of using CW-NIRS devices as a CA performance assessment tool.